Investigation of a novel type of locomotion for a snake robot suited for narrow spaces - Watanabe, M.; Khan, Md. Raisuddin (2008)
In snake robot research, one of the most efficient forms of locomotion is the lateral undulation. However, lateral undulation, also known as serpentine locomotion, is ill-suited for narrow spaces, as the body of the snake must assume a certain amount of curvature to propel forward. Other types of motion such as the concertina or rectilinear may be suitable for narrow spaces, but is highly inefficient if the same type of locomotion is used even in open spaces. Though snakes naturally can interchange between the use of serpentine and concertina movement depending on the environment, snake robots based on lateral undulation to date are unable to function satisfactorily in narrow spaces. In undergoing concertina movement, the snake lifts part of its body off the ground to reduce friction; this cannot be reproduced in planar snake robots. To overcome the inability to adapt to narrow spaces, a novel type of a gait is introduced. With slight modifications to the members of the multi-link snake robot, the robot normally developed for lateral undulation is able to utilize the new gait to negotiate narrow spaces. The modifications include alterations to the snake segments as well elements that mimic scales on the underside of the snake body. Scales, often overlooked in locomotion research, play an important role in snake movement by increasing backward and lateral friction while minimizing it in forward direction. This concept provides the basis for movement in the proposed gait. Through kinematic studies the viability of this gait is illustrated.